Beyond reformation? an essay on William Langland's Piers Plowman and the end of Constantinian Christianity - Aers, David (University of Notre Dame Press, 2015)
"In Beyond Reformation? An Essay on William Langland's Piers Plowman and the End of Constantinian Christianity, David Aers presents a sustained and profound close reading of the final version of William Langland's Piers Plowman, the most searching Christian poem of the Middle Ages in English. His reading, most unusually, seeks to explore the relations of Langland's poem to both medieval and early modern reformations together with the ending of Constantinian Christianity. Aers concentrates on Langland's extraordinarily rich ecclesiastic politics and on his account of Christian virtues and the struggles of Conscience to discern how to go on in his often baffling culture. The poem's complex allegory engages with most institutions and forms of life. In doing so, it explores moral languages and their relations to current practices and social tendencies. Langland's vision conveys a strange sense that in his historical moment some moral concepts were being transformed and some traditions the author cherished were becoming unintelligible. Beyond Reformation? seeks to show how Langland grasped subtle shifts that were difficult to discern in the fourteenth century but were to become forces with a powerful future in shaping Western Christianity"--